The origins of the dissolution of the monasteries - Hoyle, Richard (The historical journal, 1995)
The dissolution of the monasteries is one of the most familiar incidents in Tudor history. The genesis of the dissolution is however ill-documented. Here it is traced back to the suppressions of smaller houses authorized in 1528. It is shown how a partial dissolution could be construed as a desirable and necessary reform without challenging either the basis of monasticism or the doctrine of purgatory. A previously unnoticed petition is published to cast light on the anti-clerical agitation of 1529. It is suggested that there was an attempt to secure a dissolution for financial reasons in 1534 and it was the failure of this which forced the crown to adopt a new strategy to achieve a partial dissolution. This was the collection of damaging evidence of monastic corruption during the visitations of 1535. The display of this material to the Commons in 1536 persuaded them to accept a partial dissolution in the guise of a reform of monasticism. It is suggested that there was no ‘public’ demand for a dissolution in the 1530s except in the artificial circumstances of 1536, and that the shape of the dissolution was determined by the inability of government to secure the support of parliament for a dissolution justified on financial grounds.